Diagnosing diagnoses – can we improve our taxonomy? - Art Borkent (Pensoft Publishers, 2021)
Taxonomic diagnoses should be clear but minimal statements that precisely distinguish a given specimen from other taxa at the same stage of development (e.g., pupa, adult female, egg). Presently, most diagnoses are of uncertain value. It is a great advantage for readers to be able to simply and confidently confirm their identifications after using a key.